Beliefs and practices to prevent drowning among Vietnamese-American adolescents and parents. Issue 6 (14th December 2006) - Quan, L; Crispin, B; Bennett, E; Gomez, A
Abstract : Objective: To determine the beliefs, attitudes and practices regarding water safety among Vietnamese-Americans through focus group interviews. Participants: 15 teenagers (aged 15–19 years) and 20 parents participated, and reported similar attitudes, beliefs and practices regarding water activities. Participants identified a lack of familiarity with water activities and few swimming skills, noting that these activities are not perceived as recreational sports among the Vietnamese. They reported recreating at open water sites because they are free and available, and attributed drowning to fate. Vietnamese youth swim unsupervised, responding to peer pressure despite lack of skills. Participants had negative attitudes toward life jackets using, swimming pools and lessons, because of the costs, but would attend lessons in Vietnamese. They identified schools and Vietnamese media as means of delivering injury-prevention messages. Conclusions: Decreasing drowning among Vietnamese-Americans requires changing the knowledge, attitudes and safety practices with programs and messages in Vietnamese, as well as targeting the dominant culture.